The Legal Aspects of Reducing the Bureaucracy of the Court Administration - Piątek, Wojciech (Public Governance, Administration and Finances Law Review, 2018)
The article deals with questions of the bureaucratic organisation of courts, or in other words, how the court administration can affect, or is able to affect judicial autonomy, professionalism, the court’s decision making and overall the effectiveness of court functioning. The purpose of this paper is to analyse legal means of reducing the court’s bureaucracy.